How Art Therapists Observe Mental Health Using Formal Elements in Art Products: Structure and Variation as Indicators for Balance and Adaptability - Pénzes, Ingrid; Hooren, Susan van; Dokter, Ditty; Hutschemaekers, Giel (Frontiers in Psychology, 2018)
In clinical practice, formal elements of art products are regularly used in art therapy observation to obtain insight in clients’ mental health and provide directions for further treatment. Due to the diversity of formal elements used in existing studies and the inconsistency in the interpretation, it is unclear which formal elements contribute to insight into clients’ mental health. In this qualitative study using Constructivist Grounded Theory, eight art therapists were interviewed in-depth to identify which formal elements they observe, how they describe mental health and how they associate formal elements with mental health. Findings of this study show that art therapists in this study observe the combination of movement, dynamic, contour and repetition (i.e. primary formal elements) with mixture of color, figuration and color saturation (i.e. secondary formal elements). Primary and secondary elements interacting together construct the structure and variation of the art product. Art therapists rarely interpret these formal elements in terms of symptoms or diagnosis. Instead, they use concepts as balance and adaptability (i.e. self-management, openness, flexibility, and creativity). They associate balance, specifically being out of balance, with the severity of the clients’ problem and adaptability with clients’ strengths and resources. In the conclusion of the article we discuss the findings’ implications for practice and further research.